Gambaran Penggunaan Air pada Remaja di Pusat Pengembangan Anak Id-127 Kelurahan Ranomuut Kota Manado - Palandeng, Henry Malcom Frank; Sapulete, Margareth R.; Moningtja, Tyrsa; Limen, Phrycillia N.P (UNIVERSITAS SAM RATULANGI, 2013)
Background: Indonesia’s target of clean water usage in 2015 is 68.9% and 63.5% for sanitation, based on the world government’s commitment in Johannesburg on Summit 2002. According to the research by Jimmy Woodcock in 2011, only 20% of Indonesia citizens are having access to the clean water. Method: This research is aimed to know the description of water usage on teenagers in Children Development Center ID-127, Ranomuut District, Manado City. This research is a quantitative research. The population is 90 respondents consist of 41 males and 49 females, where the samples are teenagers in age’s 11-15. The data are presented by using distribution tables. Result: The research shows that 46.7% of teenagers are using water company facilitation as their source for daily needs. About 65.6% are using water filter as their drinking water source and although the 34.4% are using other sources, the water were boiled.. Most of them use the physically qualified water such as no color, no taste, no smell, and only 18.9% having several health complaints after using the water. Conclusion: Raising the awareness of teenagers about the importance of clean water by health promotion and attention from the environment may help in providing the safe and clean water for teenagers.Keywords: community, dengue fever, Knowledge, Maen village.